Metaphorical Modelling of the Concept "Technology"; Procedia - Social and Behavioral Sciences; Vol. 236 : International Conference on Communication in Multicultural Society (CMSC 2015) - Mishankina N. A. Nataliya Aleksandrovna (2016, 2016)
Title screen